Psychometric Properties of the Attitude Toward Statistics Scale on a Bangladeshi Sample - Parveen, Tahmina; Alam, Najifa; Aktar, Rumana; Ahmed, Oli (Chittagong University Journal of Biological Sciences, 2024)
Existing literature suggested the attitude toward Statistics as a predictor of academic performance in Statistics. There was an unavailability of measures for assessing attitude toward Statistics in Bangladesh. The present study was designed to adapt the Attitude toward Statistics Scale (ATSS: Wise, 1985). The adaptation procedure was done by following the guidelines of the International Test Commission (ITC). The translated ATSS was administered on a sample of 238 students from the University of Chittagong who were selected through non-probability sampling techniques. The internal consistency reliabilities, test-retest reliability, standard error of measurement, face validity, content validity, construct validity, and item response bias were estimated for assessing the psychometric properties of the Bangla ATSS. The item-total correlations, Chronbach’s Alphas, split-half reliabilities, test-retest reliability, factor loadings, and DIF contrasts suggested that this measure would be a psychometrically sound measure to apply in Bangladesh context. The Chittagong Univ. J. B. Sci.,Vol. 10(1 &2):81-94, 2020